Trading Zones: Building Connections to Past Research in the Scholarship of Teaching and Learning - Bruce Kelley (Park University, 2008)
Faculty face significant challenges when moving into scholarship of teaching and learning (SoTL) for the first time. Perhaps the greatest of these challenges is the act of building connections to past research, both within the individual scholar's field, and more broadly across the disciplines. This article examines the nature of this challenge, and how it can be partially mitigated through collaboration. The challenge, however, is monumental, and a national mandate must be issued for the creation of a scholarship of teaching and learning database that is easily accessible to faculty across the United States and the world.